Relationships between whole-body kinematics and badminton jump smash racket head speed - Miller, R.; Towler, H.; McErlain-Naylor, S.; King, M. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to identify kinematic determinants of shuttlecock speed in the badminton jump smash. Three-dimensional kinematic (400 Hz) data were collected for 18 experienced male badminton players using an 18 camera Vicon Motion Analysis System. Each participant performed 12 jump smashes. The trial with the fastest shuttlecock speed per participant was analysed using an 18-segment rigid body model. Parameters were calculated describing elements of the badminton jump smash technique. Four kinematic variables were significantly correlated with racket head speed. Greater peak wrist joint centre linear velocity, jump height, shorter acceleration phase, and greater shoulder internal rotation at shuttlecock / racket impact.